2015
DOI: 10.1039/c5tc01436k
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine-containing phenanthroimidazole electron-transport materials with electron mobility/energy-level trade-off optimization for highly efficient and low roll-off sky blue fluorescent OLEDs

Abstract: By incorporating the pyridine ring to the different position of rigid phenanthroimidazole skeleton, three new pyridine-containing phenanthroimidazole derivatives, 1-phenyl-2-(4-(pyridin-3-yl)phenyl)-1H-phenanthro[9,10-d]imidazole(CPI-p3Py), 2-phenyl-1-(4-(pyridin-3-yl)phenyl)-1H-phenanthro[9,10-d]imidazole(NPI-p3Py) and 1,2-bis(4-(pyridin-3-yl)phenyl)-1H-phenanthro[9,10-d]imidazole(CNPI-p3Py), were designed and synthesized as electron-transport materials (ETMs). Their photophysical properties, energy levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…This is ascribed to the newly generated CT owing to conjugation among the donors (triphenylamine or carbazole) and acceptor (phenanthroimidazole) as the donor moieties attached to the para carbon of thiaphenyl phenanthroimidazole. 51 New-born emitters exhibit similar absorption (sol/film) 254 (ε max = 39 370 cm –1 M –1 ), 308/252, 316 (TPNCN-TPA), and 250 (ε max = 40 000 cm –1 M –1 ), 301/246, 295 nm (TPNCN-Cz) because the core fragment is not different. The absorption from 301 and 308 nm is due to intramolecular charge transfer 52,53 from the donor (carbazole/triphenylamine) to acceptor (phenanthrimidazole).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is ascribed to the newly generated CT owing to conjugation among the donors (triphenylamine or carbazole) and acceptor (phenanthroimidazole) as the donor moieties attached to the para carbon of thiaphenyl phenanthroimidazole. 51 New-born emitters exhibit similar absorption (sol/film) 254 (ε max = 39 370 cm –1 M –1 ), 308/252, 316 (TPNCN-TPA), and 250 (ε max = 40 000 cm –1 M –1 ), 301/246, 295 nm (TPNCN-Cz) because the core fragment is not different. The absorption from 301 and 308 nm is due to intramolecular charge transfer 52,53 from the donor (carbazole/triphenylamine) to acceptor (phenanthrimidazole).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, the absorption at 300–340 nm is attributed to intramolecular CT from the donor to acceptor unit. 51 Compared with parent compounds bis phenanthrimidazoles (NPIBN, CNPIBP, and CNPIBN), D−π–A materials (TPNCN-TPA and TPNCN-Cz) show larger absorption intensity. This is ascribed to the newly generated CT owing to conjugation among the donors (triphenylamine or carbazole) and acceptor (phenanthroimidazole) as the donor moieties attached to the para carbon of thiaphenyl phenanthroimidazole.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[ 23 ] The weak shoulder at ≈363 nm should be assigned to the π – π * electronic transition of PI unit. [ 24 ] Optical bandgap ( E g ) is calculated from the threshold of its absorptions to be 3.18 eV, showing the potential to achieve deep‐blue emission in OLEDs.…”
Section: Resultsmentioning
confidence: 99%
“…All the developed electron-transport materials were purified by silica gel chromatography and then repeated thermal gradient vacuum sublimation before characterization and device fabrication. The molecular structures were confirmed by 1 H NMR, 13 C NMR and mass spectroscopy. The detailed This journal is © The Royal Society of Chemistry 2015 synthetic methods and analysis are described in the Experiment section.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Therefore, the development of electron-transport materials (ETMs) with high electron mobility and appropriate energy levels is urgent. [11][12][13] In recent years, the diphenylphosphine oxide (DPPO) group has been widely used as a unique electroactive insulating linkage. 14,15 It has been reported that its strong electron-withdrawing inductive effect can polarize molecules and enhance electron transport properties.…”
Section: Introductionmentioning
confidence: 99%